2018
DOI: 10.1038/s41467-018-05095-7
|View full text |Cite
|
Sign up to set email alerts
|

Altered thymic differentiation and modulation of arthritis by invariant NKT cells expressing mutant ZAP70

Abstract: Various subsets of invariant natural killer T (iNKT) cells with different cytokine productions develop in the mouse thymus, but the factors driving their differentiation remain unclear. Here we show that hypomorphic alleles of Zap70 or chemical inhibition of Zap70 catalysis leads to an increase of IFN-γ-producing iNKT cells (NKT1 cells), suggesting that NKT1 cells may require a lower TCR signal threshold. Zap70 mutant mice develop IL-17-dependent arthritis. In a mouse experimental arthritis model, NKT17 cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 68 publications
5
70
0
Order By: Relevance
“…Overall, this suggests a potential requirement for different TCR signal intensities in the development of each (Figure 2). In fact, two independent groups recently addressed this question by exploiting the SKG mouse model, in which TCR signaling is weakened because of a hypo-morphic ZAP70 allele 54,56 . Hence, both studies showed that weakened TCR signaling led to abrogation in NKT2 and, to a lesser extent, NKT17 cell development while not reducing NKT1 cell development.…”
Section: Tcr Signaling: Strength and Contextmentioning
confidence: 99%
“…Overall, this suggests a potential requirement for different TCR signal intensities in the development of each (Figure 2). In fact, two independent groups recently addressed this question by exploiting the SKG mouse model, in which TCR signaling is weakened because of a hypo-morphic ZAP70 allele 54,56 . Hence, both studies showed that weakened TCR signaling led to abrogation in NKT2 and, to a lesser extent, NKT17 cell development while not reducing NKT1 cell development.…”
Section: Tcr Signaling: Strength and Contextmentioning
confidence: 99%
“…For instance, in support of thymic commitment it has been shown that the TCR signal strength during thymic development can direct the differentiation of iNKT cells within specific functional subsets . Further to this, a variety of signalling molecules and transcription factors including Zap70, Bcl11b or Roquin has been shown to participate in the control of iNKT cell lineage differentiation . On the other hand, several lines of evidence suggest that iNKT cells can acquire functional capabilities in the periphery.…”
Section: Nkt Cells: An Overviewmentioning
confidence: 99%
“…Recent evidence has identified altered TCR signal strength as a regulator of iNKT cell effector subset development, with decreased TCR signal strength leading to a predominance of iNKT1 cells, while strong TCR signal strength enhances iNKT2 and iNKT17 cell development (Tuttle et al, 2018; Zhao et al, 2018). The induction of Mob1 (Thr35) phosphorylation downstream of TCR/CD28 signaling occurred in an Mst1-dependent manner (Fig.…”
Section: Resultsmentioning
confidence: 99%